Suitability of three eriophyid mites as prey for the predatory mite, Typhlodromus athiasae (Acari: Phytoseiidae) - Shimaa F. Fahim; Faten M. Momen (Persian Journal of Acarology)
The eriophyid mites, Aceria kenyae (Keifer), A. mangiferae Sayed, and Calepitrimerus baileyi Keifer are important phytophagous pests in Egypt. In this study, the effect of the above-mentioned eriophyids, as natural prey, on the biological and population growth parameters of the phytoseiid mite, Typhlodromus athiasae Porath & Swirski was evaluated. This phytoseiid can successfully develop and reproduce on A. kenyae, A. mangiferae, and C. baileyi. Individuals of T. athiasae fed on A. mangiferae displayed the shortest pre-adult development, while those fed on A. kenyae and C. baileyi took more time to reach the adult stage. Adult female longevity of T. athiasae was longer on A. mangiferae (36.79 days) than on A. kenyae (31.65 days) and C. baileyi (31.18 days). The total number of eggs per T. athiasae female was the highest on A. mangiferae, followed by A. kenyae, and C. baileyi (46.29, 37.62, and 34.39 eggs/female, respectively). Presently, feeding of T. athiasae on A. mangiferae resulted in the maximum intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rate (R0) as compared to the other prey. In addition, preying on A. mangiferae showed the shortest mean generation time (T), while A. kenyae showed the longest one as prey of T. athiasae. In conclusion, the present results showed that the T. athiasae population could display a high capacity to increase when preying on the tested eriophyids (especially on A. mangiferae). So, this predator may be capable of providing effective management of these eriophyid mites.